Execution of Fiduciary Guarantees against Defaulting Debtors Who Resist the Execution - Taradipa, Tania (TABELLIUS: Journal of Law, 2023)
This research aims to determine the obstacles in the implementation of the fiduciary guarantee execution process. As well as to find out the efforts made by the bank in carrying out the execution process. Method The approach in this research is the Sociological Juridical research method. This research specification uses descriptive analysis. The type of data used in this research is primary data including Law Number 42 of 1999 concerning Fiduciary Guarantees, the Civil Code, as well as secondary data containing documents and other supports. Collecting research data using interview techniques and studying documents or library materials. The data analysis method used in analyzing the data is qualitative analysis. The results of this research are: (1) The executive power possessed by the Fiduciary Guarantee is the same as a court decision which has permanent legal force, this is because the Object of the Fiduciary Guarantee has included instructions which read "For the sake of Justice Based on Belief in One Almighty God". Obstacles and solutions found in the process of executing fiduciary collateral objects include resistance from the executed party through civil lawsuits, through debt acknowledgment letters, and through selling collateral carried out privately or through an auction. Keywords: Agreement; Credit; Executorial; Fiduciary; Guarantee.